2014
DOI: 10.1182/blood-2013-10-534735
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Prdm16 mRNA is a specific antileukemic mechanism during HOXB4-mediated HSC expansion in vivo

Abstract: Key Points HOXB4 induces stable gene expression changes in transplanted HSCs that drive balanced self-renewal and differentiation divisions. Marked downregulation of Prdm16 occurs concurrently with HOXB4-mediated HSC expansion and functions to prevent leukemia in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
(50 reference statements)
2
16
1
Order By: Relevance
“…Expression of NID2 suppresses migration and inhibits metastasis by suppressing the EGFR/AKT and integrin/FAK/PLCγ pathways . HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto‐oncogene necessary for self‐renewal and maintenance of murine hematopoietic stem cells . The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129–2) confirmed in our study have also shown hypermethylation in other malignancies (Table ) .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Expression of NID2 suppresses migration and inhibits metastasis by suppressing the EGFR/AKT and integrin/FAK/PLCγ pathways . HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto‐oncogene necessary for self‐renewal and maintenance of murine hematopoietic stem cells . The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129–2) confirmed in our study have also shown hypermethylation in other malignancies (Table ) .…”
Section: Discussionsupporting
confidence: 81%
“…32 HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto-oncogene necessary for self-renewal and maintenance of murine hematopoietic stem cells. 33 The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129-2) confirmed in our study have also shown hypermethylation in other malignancies (Table 1). [34][35][36][37][38][39][40][41][42] Among them, SFMBT2 and MIR129-2 have been shown to act as tumor suppressors.…”
Section: Discussionsupporting
confidence: 79%
“…PGC1 and MED1) (data not shown), it is likely that the intrinsic activity of the PR domain is specifically required for tumor suppression function of PRDM16. Several previous studies have shown that overexpression of PR-less PRDM16S isoform, but not PRDM16, is leukemogenic: 1) leukemogenic translocation in AMLs mostly involves PRDM16S, but not full length PRDM16 (Quentin et al, 2011; Shimizu et al, 2000); 2) PRDM16S is selectively overexpressed in adult T cell leukemia (Yoshida et al, 2004); 3) aberrant expression of PRDM16S by retroviral insertion promotes immortalization of murine bone marrow progenitors and blocks granulocytic differentiation (Du et al, 2005a; Nishikata et al, 2003); 4) overexpression of Prdm16S in p53 null bone marrow cells induces AML with full penetrance (Shing et al, 2007); and 5) overexpression of both Prdm16S and Hoxb4 led to myeloid expansion and leukemia (Yu et al, 2014). These studies suggest that loss of the PR-domain is compatible with leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…IRX1 activates HOXB4 which is on the apex of an important stem cell program that allows the maintenance and expansion of stem cells [4549]. It is highly likely that this mechanism is necessary to induce and maintain leukemic stem cells.…”
Section: Discussionmentioning
confidence: 99%